A política de fechamento de escolas no campo na Região Metropolitana de Curitiba - Pereira, Camila Casteliano (2017)
This research problematizes the schools closing in the Metropolitan Region of Curitiba (Parana State, Brazil). It aims to analyze the policy of closing public schools located in the countryside in the Metropolitan Region of Curitiba and understand which the motivations for this policy are. This research is based on historical-dialectical materialism using the method of quantitative-qualitative approach, with the following procedures: 1) collection of documentary data of the Metropolitan Region of Curitiba 2) documentary analysis of the documents that register the closing of rural schools, and the Guidelines of countryside Education, 3) bibliographical review, 4) theoretical discussion considering reference authors. The fundamental category of analysis is contradiction. It was observed that the closure of schools located in the metropolitan region is an expression of the concept of Rural Education, since it is carried out from the governmental sphere. It was observed the existence of educational policies that leads to the closing of schools and can be highlighted: the policy to consolidate isolated schools until the decade of 1985, the policy of school centralization and children transport to school. This situation is due to the existing field project, closely linked to the capitalist production structure. In this sense the closing of schools is the result of a field option, taking into consideration the concentration of land and wealth generates inequalities and express negative consequences to peasants. It can be seen that the policy of closing schools in the Metropolitan Region of Curitiba is marked by several motivations: political, social and economic. These include: the advance of capitalist agriculture, the promotion of children transport to school policy, the denial of peasant social practices, the lack of attention from the governmental sphere, the similarity with urban-centric pedagogical practices that deny the potential of a work focused on human formation, demobilization of community about school issues. We believe that in order to modify such relationships it is necessary to mobilize the subjects of the field. It is necessary to act from the context and reflect on it by democratically incorporating the social function of the school in dialogue, regarding the principles of countryside Education.